Politik Identitas dan Perilaku Pemilih pada Pilpres 2019: Studi di Kota Palembang Sumatera Selatan - Fadil Ainur Rif'an (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) UIN Walisongo, 2020)
This study describes the pattern of relations between identity politics and voter behavior at the local level in contemporary Indonesia. This study focuses on the widespread use of religion-based identity politics used by supporters of presidential and vice-presidential candidates and its influence on voter behavior in urban communities in Palembang City in the 2019 Presidential Election. qualitative research, this study aims to answer the following two key questions. First, how is religion-based identity politics used to mobilize voters in the 2019 Presidential Election in Palembang City? and how does the use of identity politics affect voter behavior in the city of Palembang in the 2019 presidential election? The results of this study found two things. First, religion-based identity politics was used in a structured and systematic way in the 2019 presidential election by local religious leaders who supported the No. 2 pair, namely Prabowo Subianto and Sandiaga Uno. The politicization of religious symbols in the pulpits of da'wah and the use of verses from the Qur'an and Hadith are used to build public discourse that providing support to couple No. 2 is part of the struggle and jihad to defend Allah's religion. Second, the use of ulama and religious verses as instrumentation in the campaign has influenced public opinion and preference in the 2019 presidential election, both from the upper-middle class and lower-class groups in Palembang City.